STRUKTUR KOMUNITAS DAN PRODUKTIVITAS EKOSISTEM PADANG LAMUN DI PULAU PANNIKIANG SULAWESI SELATAN - Lizha Dwi Mulya Putri; Abdul Rauf; Hamsiah Hamsiah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
This research was conducted with the aim of: Analyzing community structure and productivity of seagrasses. The research was conducted in August to November 2018. Data analysis included community structure analysis and seagrass productivity, then tested using One-Way ANOVA and Duncan's advanced test using the SPSS version 15 program. The results of this study indicate that: Seagrass communities on Pannikiang Island consist of the types Enhalus acoroides, Halophila ovalis, and Cymodocea rotundata, which are dominated by Enhalus acoroides. The type of muddy substrate and seen from its nutrient content, can be categorized in water conditions that are suitable for seagrass life. The result of INP calculation is dominated by Enhalus acoroides, while the highest productivity (biomass) is found in the type of Enhalus acoroides.